Acute megakaryoblastic leukemia mimicking small round cell tumor with novel t(1;5)(q21;p13) - BOZKURT, SÜHEYLA (BLACKWELL PUBLISHING, 2008)
Acute megakaryoblastic leukemia is a relatively rare form of acute leukemia that has heterogeneous blast morphology and karyotypic abnormalities. An 8-month-old boy with a retroperitoneal mass was diagnosed as having acute megakaryoblastic leukemia that initially presented as small round cell tumor of childhood. Bone marrow aspiration showed syncytial groups of atypical medium sized cells with scant cytoplasm and fine nuclear chromatin. Retroperitoneal mass biopsy showed several lymph nodes with cohesive clusters of neoplastic cells that demonstrated expression of Factor VIII. Flow cytometric analysis of the second bone marrow aspiration showed CD 61 positivity. Karyotypic analysis of bone marrow cells showed a novel translocation, (1;5)(q21;p13).
Keywords: acute megakaryoblastic leukemia; small round cell tumor; metastatic carcinoma; cytogenetics; t(1;5); SIMULATING METASTATIC TUMOR; TRANSLOCATION; CHILDREN; INFANTS; GENE